2007
DOI: 10.1016/j.ejcts.2007.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for airway complications within the first year after lung transplantation

Abstract: Objective: Lung transplantation (LTx) has enjoyed increasing success with better survival in recent years. Nevertheless, airway anastomotic complications (AC) are still a potential cause of early morbidity and mortality. In this retrospective cohort study we looked at possible predictors of AC within the first year after LTx. Methods: Between July 1991 and December 2004, 232 consecutive single (n = 102) and bilateral (n = 130) LTx were performed (142 males and 90 females; mean age: 48 years [range 15-66 years]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 22 publications
6
104
1
3
Order By: Relevance
“…It has been associated with decreased lung function and worse survival [5,6,32]. It is also associated with prolonged mechanical ventilation, hospital and ICU length of stay, increased cost, and poor QOL [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with decreased lung function and worse survival [5,6,32]. It is also associated with prolonged mechanical ventilation, hospital and ICU length of stay, increased cost, and poor QOL [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have shown that infection with Aspergillus or Pseudomonas cepacia is a risk factor for AC. 3,10 In fact, in the present series the patients affected by stenosis were infected with Aspergillus terreus or MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 According to recent reports, the incidence of ACs requiring intervention ranges from 7% to 15.7%, and 2.5%-4% of transplant patients die of ACs, which shows that further improvements are needed to promote bronchial healing. 3,4 Living-donor lobar lung transplantation (LDLLT) was developed at the University of Southern California, and has been established as a safe and reproducible procedure to deal with the shortage of cadaveric donors. 5,6 Considering the severity of the recipient's illness and the urgent nature of the transplantation, the recipient outcomes of LDLLT have been reported to be similar to or better than those of CLT.…”
Section: Introductionmentioning
confidence: 99%
“…Wauwer и соавт. показали, что факто-рами риска развития бронхиальных осложнений в первый год после трансплантации легких являются применение техники телескопического анастомоза, а также рост реципиента и время искусственной вентиляции легких у донора [10]. Также многие ав-торы придают важную роль в формировании стено-зов инфекционным и воспалительным процессам в трахеобронхиальном дереве донорских легких как на стадии кондиционирования, так и после выпол-нения трансплантации [2,11].…”
Section: Discussionunclassified